CLEC9A modulates macrophage-mediated neutrophil recruitment in response to heat-killed Mycobacterium tuberculosis H37Ra - Cheng, An-Chieh; Yang, Kuang-Yao; Chen, Nien-Jung; Hsu, Tsui-Ling; Jou, Ruwen; Hsieh, Shie-Liang; Tseng, Ping-Hui (PloS one, 2017)
Tuberculosis is a fatal human infectious disease caused by Mycobacterium tuberculosis (M. tuberculosis) that is prevalent worldwide. Mycobacteria differ from other bacteria in that they have a cell wall composed of specific surface glycans that are the major determinant of these organisms' pathogenicity. The interaction of M. tuberculosis with pattern recognition receptors (PRRs), in particular C-type lectin receptors (CLRs), on the surface of macrophages plays a central role in initiating innate and adaptive immunity, but the picture as a whole remains a puzzle. Defining novel mechanisms by which host receptors interact with pathogens in order to modulate a specific immune response is an area of intense research. In this study, based on an in vitro lectin binding assay, CLEC9A (DNGR-1) is identified as a novel CLR that binds with mycobacteria. Our results with CLEC9A-knocked down cells and a CLEC9A-Fc fusion protein as blocking agents show that CLEC9A is involved in the activation of SYK and MAPK signaling in response to heat-killed M. tuberculosis H37Ra treatment, and it then promotes the production of CXCL8 and IL-1β in macrophages. The CXCL8 and IL-1β secreted by the activated macrophages are critical to neutrophil recruitment and activation. In a in vivo mouse model, when the interaction between CLEC9A and H37Ra is interfered with by treatment with CLEC9A-Fc fusion protein, this reduces lung inflammation and cell infiltration. These findings demonstrate that CLEC9A is a specialized receptor that modulates the innate immune response when there is a mycobacterial infection.